The role of improving tax relation for the growth of agricultural production - Ahrorov Zarif; Yekimov Sergey; Tuychiev Sherkhon; Ortikov Akhmadjon (E3S Web of Conferences, 2023)
Considering taxes to be the universally recognized regulator of the economy, related ideas on the proper organization of tax relations are being promoted in various scientific papers. The relevance of this problem is caused, firstly, by the choice of a model of tax regulation within the framework of the general economic situation, by thoughts that are about “tax relations”, “principles of taxation”, “mechanism taxation”, “about the nature of the tax”, and secondly the within the framework of the tax system operating in the Republic of Uzbekistan, the instruments of tax relations are characterized by high economic inefficiency. The purpose of this research is to generalize the works on tax relations, improve tax regulation, develop the necessary proposals and recommendations to enhance the role of tax regulation mechanisms in the framework of improving tax policy that aimed at ensuring high economic growth. The paper also analyzes theories of tax regulation in the framework of using tax regulation mechanisms in order to ensure the growth of income (profit) of economic entities with a simultaneous decrease in the share of tax revenues in GDP. By defining the economic boundaries of tax policy, it is possible to solve not only the problems of economic growth of the country as whole, but also social issues in changing economic conditions. The paper also analyzes the opinions of various domestic and foreign economists on tax relations.